2024
DOI: 10.1111/1471-0528.17756
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to microplastics and human reproductive outcomes: A systematic review

Kathryn Hunt,
Anna Davies,
Abigail Fraser
et al.

Abstract: BackgroundMicroplastics, produced through degradation of environmental plastic pollution, have been detected in human tissues including placenta and fetal meconium. Cell culture and animal studies have demonstrated potential reproductive toxicity of these particles; however, their association with adverse fertility or pregnancy outcomes in humans is not known.ObjectivesTo synthesise evidence for the presence of microplastics in human reproductive tissue and their associations with environmental exposures and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…People across the world come into close, daily contact with plastics and the byproducts of their disintegration, especially nano-and microplastics. The discovery of microplastics in the placenta has sparked worries that plastics might affect fetal growth during pregnancy [16,[21][22][23][24][25][26][27][28][29]. Plastic pollution is a serious and growing worldwide issue; by 2060, the amount of plastic that leaks into the environment is expected to have doubled to 44 million tons annually from 22 million tons in 2019 [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…People across the world come into close, daily contact with plastics and the byproducts of their disintegration, especially nano-and microplastics. The discovery of microplastics in the placenta has sparked worries that plastics might affect fetal growth during pregnancy [16,[21][22][23][24][25][26][27][28][29]. Plastic pollution is a serious and growing worldwide issue; by 2060, the amount of plastic that leaks into the environment is expected to have doubled to 44 million tons annually from 22 million tons in 2019 [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated that MPs cause harm to reproductive systems in several animal species and significantly affect the anomalies of development and metabolism in progeny [2,8,10,11,28,37]. A worldwide health concern, female reproductive disorders may have a direct correlation to the state of the environment [16]. Furthermore, prenatal exposure to these chemicals is especially concerning for the health and development of the unborn child because pregnancy is a critical time for the development of newborn organs [37].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations